(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present study focuses on the zooplanktonic diversity of Rajsamand Lake. Zooplankton aresmall aquatic animals that are free-floating in the water. They are an important component of the lakeecosystem, and play a key role in the food chain. The study of zooplanktonic diversity provides valuableinformation about the health of the lake ecosystem. The analysis of water variables such as ,temperature(from thermometer) ,pH(electronic handy digital pH meter) ,depth of visibility (from sachhidisc ), TDS(from digital TDS meter) Dissolved oxygen (digital dissolved oxygen meter) at the station ofthe study as well as winklers methods in the lab . Alkalinity (through titration) ,hardness(throughtitration) , sulphate by accordance to IS3025 APHA 20TH EDITION an d EPA-6004-79-020USEPA method375.4,phosphate,nitrogen-nitrate,sulphate by spectrophotometer titration were measured in thelaboratory within the period of 24 hrs of sample collection. Studies of zooplankton diversity wereconducted at five different locations on Rajsamand Lake (S, I, S, S, and S, V). During the first year of thestudy (2019-2020), a total of 39 species were recorded these belonged to four different taxonomicgroups.